Purification of carbon nanotubes - Hou, Peng-Xiang; Liu, Chang; Cheng, Hui-Ming (Carbon (New York), 2008)
It is predicted theoretically and understood experimentally that carbon nanotubes (CNTs) possess excellent physical and chemical properties and have wide-range potential applications. However, only some of these properties and applications have been verified or realized. To a great extent, this situation can be ascribed to the difficulties in getting high-purity CNTs. Because as-prepared CNTs are usually accompanied by carbonaceous or metallic impurities, purification is an essential issue to be addressed. Considerable progress in the purification of CNTs has been made and a number of purification methods including chemical oxidation, physical separation, and combinations of chemical and physical techniques have been developed for obtaining CNTs with desired purity. Here we present an up-to-date overview on the purification of CNTs with focus on the principles, the advantages and limitations of different processes. The effects of purification on the structure of CNTs are discussed, and finally the main challenges and developing trends on this subject are considered. This review aims to provide guidance and to stimulate innovative thoughts on the purification of CNTs.